(untitled) (Alexandria, Va., 1991)
This book introduction the world of war games, electronic sentinels, a new age in weaponry, the computer an C3
Keywords: Military art and science,Military art and science,Khoa học nghệ thuật quân sự,Khoa học nghệ thuật quân sự; Data processing,Automation,Xử lý dữ liệu,Tự động hóa